Effects of Kombucha on oxidative stress induced nephrotoxicity in rats - Gharib Ola (BMC, 2009)
Abstract Background Trichloroethylene (TCE) may induce oxidative stress which generates free radicals and alters antioxidants or oxygen-free radical scavenging enzymes. Methods Twenty male albino rats were divided into four groups: (1) the control group treated with vehicle, (2) Kombucha (KT)-treated group, (3) TCE-treated group and (4) KT/TCE-treated group. Kidney lipid peroxidation, glutathione content, nitric oxide (NO) and total blood free radical concentrations were evaluated. Serum urea, creatinine level, gamma-glutamyl transferase (GGT) and lactate dehydrogenase (LDH) activities were also measured. Results TCE administration increased the malondiahyde (MDA) and NO contents in kidney, urea and creatinine concentrations in serum, total free radical level in blood and GGT and LDH activities in serum, whereas it decreased the glutathione (GSH) level in kidney homogenate. KT administration significantly improved lipid peroxidation and oxidative stress induced by TCE. Conclusion The present study indicates that Kombucha may repair damage caused by environmental pollutants such as TCE and may be beneficial to patient suffering from renal impairment.